Bipolar disorder - difficulties in managing emotional ups and down in an entertainer life: a case report - Wulandari, Arlisa; D Kusuma, Meily; Pancarani, Rachmaditya (ACTA Medical Health Sciences, 2023)
Bipolar disorder is a chronic and recurrent disorder, a brain disorder that causes changes in a person’s mood, energy, and ability to function. Patients have alternate increased mood and activities (mania, hypomania, or “ups” period) and declining mood and activities (depressive or “downs” period) in their life. Symptoms of the manic episodes of bipolar disorder include sensitive feelings, lack of rest, and shot up self-esteem, while the depressive episodes bring loss of interest, more or less sleep than usual, anxiety, a feeling of worthlessness, and lack of concentration. Bipolar disorder is a severe mental disorder with a fairly high prevalence of 1%- 2% and is the 5th cause of disability in the world. Many factors have been considered to contribute to this disorder. While there is strong evidence that some genetic and environmental factors are associated with bipolar disorder, only a few can provide sufficient evidence to establish causality. This report discusses the case of a new manic episode of bipolar disorder that occurs in a woman aged 25 years old who works as a public figure, announcer, and entertainer. The patient has been hospitalized several times and received various pharmacotherapy and psychotherapy but still having difficulties in managing the ups and downs of her emotion. A lot of individual factors must be considered in managing patients with bipolar disorder DOI : 10.35990/amhs.v1n3.p137-143 REFERENCES Shang, Y., & Shi, Z. (2020). Rural-urban migration and migrants’ mental health: Based on the analysis of CLDS data. Northwest Population Journal, 41, 104–113. Vos, T., Barber, R. M., Bell, B., Bertozzi-Villa, A., Biryukov, S., Bolliger, I., Charlson, F., Davis, A., Degenhardt, L., Dicker, D., et al. (2015). Global, regional, and national incidence, prevalence, and years lived with disability for 301 acute and chronic diseases and injuries in 188 countries, 1990–2013: A systematic analysis for the Global Burden of Disease Study 2013. The Lancet, 386, 743–800. Pusat Data dan Informasi Kementerian Kesehatan RI. (2019). Situasi Kesehatan Jiwa di Indonesia. Chou, P. H., Tseng, W. J., Chen, L. M., Lin, C. C., Lan, T. H., & Chan, C. H. (2015). Late onset bipolar disorder: A case report and review of the literature. Journal of Clinical Gerontology and Geriatrics, 6, 27–29. Maslim, R. (2003). Diagnosis Gangguan Jiwa: Rujukan Ringkas PPDGJ III. Jakarta: Bagian Ilmu Kedokteran Jiwa FK Unika Atma Jaya. Dell’Osso, L., Pini, S., Cassano, G. B., Mastrocinque, C., Seckinger, R. A., & Saettoni, M. (2002). Insight into illness in patients with mania, mixed mania, bipolar depression, and major depression with psychotic features. Bipolar Disorders, 4, 315–322. Centers for Disease Control and Prevention (CDC). (2011). Mental illness surveillance among adults in the United States. MMWR. Dattani, S., Ritchie, H., & Max, R. (2021). Mental Health. Our World in Data. Retrieved March 21, 2022, from https://ourworldindata.org/mental-health Fiorillo, D., Lubrano Lavadera, G., & Nappo, N. (2020). Structural social capital and mental health: A panel study. Applied Economics, 52, 2079–2095. Donkin, A., Goldblatt, P., Allen, J., Nathanson, V., & Marmot, M. (2017). Global action on the social determinants of health. BMJ Global Health, 2. Han, J., Jia, P., Huang, Y., Gao, B., Yu, B., Yang, S., Yu, J., Xiong, J., Liu, C., Xie, T., et al. (2020). Association between social capital and mental health among older people living with HIV: The Sichuan Older HIV-Infected Cohort Study (SOHICS). BMC Public Health, 20, 581. Lu, N., & Zhang, J. (2019). Social capital and self-rated health among older adults living in urban China: A mediation model. Sustainability, 11, 5566. Le, Z., & Liang, H. (2020). The impact of social capital on individual health of the rural elderly. Journal of South China Agricultural University, 19, 34–45. Mohan, I., & Sagar, R. (2006). Chronic mania: An unexpectedly long episode. Indian Journal of Medical Sciences, 60(5). Smoller, J. W., & Finn, C. T. (2003). Family, twin, and adoption studies of bipolar disorder. American Journal of Medical Genetics Part C: Seminars in Medical Genetics, 123C, 48–55.